Association between obstructive sleep apnea and albuminuria in Korean adults: a nationwide population-based study - Yeojin Yu; Kyungdo Han; Kyu-na Lee; Jung Hun Koh; Young Sun Shin; Jeong Min Cho; Minsang Kim; Min Woo Kang; Seong Geun Kim; Sehyun Jung; Semin Cho; Hyuk Huh; et al. (Kidney Research and Clinical Practice, 2024)
Background Obstructive sleep apnea (OSA) is a sleep disorder associated with an increased risk of cardiovascular and metabolic complications. Albuminuria, an early marker of kidney damage, is a proposed risk factor for OSA and its adverse outcomes. The study explored the association between OSA and albuminuria in Korean adults. Methods We screened participants from the cross-sectional Korean National Health and Nutrition Examination Survey (2019- 2021). The study included participants aged 40 years and older who completed the STOP-BANG questionnaire, a tool used to assess the OSA risk. Albuminuria was defined as a urine albumin-to-creatinine ratio ≥30 mg/g Cr. The participants were categorized based on albuminuria presence and severity. A multivariate logistic regression analysis examined the association between albuminuria and OSA. Results This study included 10,923 participants. Participants with albuminuria had significantly higher STOP-BANG scores than those without. Moreover, albuminuria remained strongly associated with an increased risk of OSA (odds ratio, 2.01; 95% confidence interval, 1.66-2.43), after multivariate adjustment. This association was more pronounced as albuminuria severity increased. Participants with high STOP-BANG scores were more likely to have albuminuria (odds ratio, 2.51; 95% confidence interval, 1.89-3.31), highlighting the bidirectional relationship between albuminuria and OSA. Conclusion The present study demonstrated a significant association between albuminuria and an elevated risk of OSA. These findings underscore the importance of early screening for OSA in patients with albuminuria, particularly in those with additional metabolic risk factors, to improve their long-term outcomes.